Association between HULC rs7763881 and cancer risk: an updated Meta-analysis. (1st December 2021) - Gao, Xueren; Yang, Jiaxin; Wang, Dongbo; Zeng, Qinghang; Li, Fangting; Zhou, Sasha; Zhang, Xue; Fan, Chen; Gao, Ziyan; Zhao, Yining
Abstract: In recent years, several case-control studies have explored the association between the rs7763881 locus polymorphism of the HULC gene and cancer risk, however, the findings have been inconsistent. Therefore, a meta-analysis was conducted to clarify the association. Relevant case-control studies were obtained from CNKI, Embase, Web of Science and PubMed databases. RevMan software was used to perform data analysis. A total of 8 case-control studies containing 4036 cases and 5286 controls were included in the current meta-analysis. The overall analysis results showed no significant association between the rs7763881 locus polymorphism and cancer risk. However, stratified analysis based on cancer type showed that the rs7763881 locus polymorphism was associated with the decreased risk of hepatocellular cancer, colorectal cancer and esophageal cancer. In conclusion, the current findings suggest that the rs7763881 polymorphic loci located on the HULC gene may serve as a biomarker for determining an individual's risk of hepatocellular cancer, colorectal cancer and esophageal cancer.